URGENSI KEBUTUHAN AKTAAUTENTIK DI MASA PANDEMI COVID-19 - Andi Suci Wahyuni (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The economic stimulus policy places an additional burden on its implementation for financial institutions to restructure and renegotiate agreements, so that the need for authentic deeds as evidence becomes the urgency. This study aimed to determine to which Indonesian laws and regulations already accommodated the transformation of notarial deeds in electronic systems and teleconferencing media can be used. This research was conducted with a normative research method and with a conceptual approach to an authentic deed based on the Civil Law system and the statue approach. The results of this study indicate that the need for authentic deeds, in this case, is needed even though the Covid-19 pandemic period is still ongoing. The need for authentic deeds is the main document to strengthen one's position concerning the right of interest before the court. It cannot be predicted how long the pandemic will last. After pandemic, the changes in the way of life will proceed as before. Direct interaction, face to face, and physical presence are not the crucial things in establishing legal relations. Transforming procedures for making authentic deeds by notaries and other public officials need to be done to provide a legal data and supporting facilities so that the transformation of electronic data establishment and filling for the authentic deed and PPATdeed are carried out